Supramolecular Chromatographic Separation of C60 and C70 Fullerenes: Flash Column Chromatography vs. High Pressure Liquid Chromatography - Mekapothula, Subbareddy; Wonanke, A. D. Dinga; Addicoat, Matthew A.; Boocock, David J.; Wallis, John D.; Cave, Gareth W. V. (International journal of molecular sciences, 2021)
A silica-bound C-butylpyrogallol[4]arene chromatographic stationary phase was prepared and characterised by thermogravimetric analysis, scanning electron microscopy, NMR and mass spectrometry. The chromatographic performance was investigated by using C60 and C70 fullerenes in reverse phase mode via flash column and high-pressure liquid chromatography (HPLC). The resulting new stationary phase was observed to demonstrate size-selective molecular recognition as postulated from our in-silico studies. The silica-bound C-butylpyrogallol[4]arene flash and HPLC stationary phases were able to separate a C60- and C70-fullerene mixture more effectively than an RP-C18 stationary phase. The presence of toluene in the mobile phase plays a significant role in achieving symmetrical peaks in flash column chromatography.